Bioequivalence and Food Effect Assessment of Two Fixed‐Dose Combination Formulations of Telmisartan‐Hydrochlorothiazide Tablets in Chinese Healthy Subjects - Hu, Minwan; Yang, Man; Zhang, Shuyu; Li, Jiangfan; Pang, Hongxian; Pei, Yingzi; Guo, Chao; Wang, Xuhong (Clinical and translational science, 2025)
ABSTRACT This study assessed the bioequivalence and food effect of two fixed‐dose combination (FDC) formulations of telmisartan‐hydrochlorothiazide tablets (telmisartan 40 mg, hydrochlorothiazide 12.5 mg) in healthy Chinese subjects. Seventy‐two subjects were enrolled and divided into fasted and fed cohorts in a single‐center, randomized, open‐label, single‐dose, three‐period, three‐sequence, and crossover study. The pharmacokinetic characteristics of telmisartan and hydrochlorothiazide, including Cmax and AUC, were compared after subjects received single oral doses of telmisartan‐hydrochlorothiazide tablets using a validated LC–MS/MS method. Safety and tolerability of treatments were monitored. Pharmacokinetic profiles of two FDC telmisartan‐hydrochlorothiazide tablets were comparable after single‐dose administration. 90% CI of geometric mean ratios (GMRs) of AUC0‐t, AUC0‐∞, and Cmax of telmisartan and hydrochlorothiazide of two FDC formulations fell within the predefined bioequivalence range of 80.0%–125.0% under both fasted and fed conditions. Administration with food had significant effects on telmisartan pharmacokinetic parameters but a slight impact on hydrochlorothiazide. Notably, Cmax and AUC of telmisartan were significantly decreased by 39.6%–43.7% in the fed versus fasted conditions. Safety assessments revealed all treatments were safe and well tolerated. Two telmisartan‐hydrochlorothiazide FDC formulations were bioequivalent in healthy Chinese subjects in both fasted and fed states. All treatments were well tolerated.